Monitoring levels of circulating cell‐free DNA in patients with metastatic colorectal cancer as a potential biomarker of responses to regorafenib treatment. Issue 9 (22nd June 2021) - Pastor, Brice; André, Thierry; Henriques, Julie; Trouilloud, Isabelle; Tournigand, Christophe; Jary, Marine; Mazard, Thibault; Louvet, Christophe; Azan, Simon; Bauer, Audrey; Roch, Benoit; Sanchez, Cynthia; et al.
Abstract : Circulating cell‐free DNA (cfDNA) contains circulating tumor DNA (ctDNA), which can be obtained from serial liquid biopsies to enable tumor genome analysis throughout the course of treatment. We investigated cfDNA and mutant ctDNA as potential biomarkers to predict the best outcomes of regorafenib‐treated metastatic colorectal cancer (mCRC) patients. We analyzed longitudinally collected plasma cfDNA of 43 mCRC patients prospectively enrolled in the phase II TEXCAN trial by IntPlex qPCR. Qualitative ( KRAS, NRAS, BRAF V600E mutations) and quantitative (total cfDNA concentration, mutant ctDNA concentration, mutant ctDNA fraction) parameters were correlated with overall survival (OS) and progression‐free survival (PFS). When examined as classes or continuous variables, the concentrations of total cfDNA, mutant ctDNA, and, partly, mutant ctDNA fraction prior to regorafenib treatment correlated with OS. Patients with baseline cfDNA > 26 ng·mL −1 had shorter OS than those with cfDNA value below this threshold (4.0 vs 6.9 months; log‐rank P = 0.0366). Patients with baseline mutant ctDNA > 2 ng·mL −1 had shorter OS than those with mutant ctDNA below this threshold (log‐rank P = 0.0154). We show that pretreatment cfDNA and mutant ctDNA levels may identify mCRC patients that may benefit from regorafenib treatment. Abstract : Circulating cell‐free DNA (cfdNA) was extracted from longitudinal blood collection of 43 mCRC patients treated by regorafenib. Qualitative ( RAS, BRAF V600E mutations) and quantitative (cfDNA concentration, mutant circulating tumor DNA (ctDNA) concentration, mutant ctDNA fraction) parameters were correlated with survival. We show that pretreatment cfDNA and mutant ctDNA levels may identify mCRC patients that may benefit from regorafenib treatment.